Effect of Wrapped Carbon Nanotubes on Optical Properties, Morphology, and Thermal Stability of Electrospun Poly(vinyl alcohol) Composite Nanofibers. (6th June 2013) - Diouri, Naoual; Baitoul, Mimouna; Maaza, Malik
Abstract : Electrospinning was used to elaborate poly(vinyl alcohol) (PVA) nanofibers in the presence of embedded multiwall carbon nanotubes (MWCNTs) in surfactant and polymer. MWCNTs were dispersed in aqueous solution using both sodium dodecyl sulfate (SDS) as surfactant and Poly(vinyl pyrrolidone) (PVP). Changing the surfactant and polymer concentration reveals that the maximum dispersion achievable is corresponding to the mass ratios MWCNTs : SDS—1 : 5 and MWCNTs : SDS : PVP—1 : 5 : 0.6 in the presence of the PVP. After the optimization of the dispersion process, the SEM image of the PVA/PVP/SDS/MWCNTs electrospun fibers presents high stability of the fibers with diameter around 224 nm. Infrared spectroscopy and thermal gravimetric analysis elucidate the type of interaction between the PVA and the coated carbon nanotube. The presence of PVP wrapped carbon nanotubes reduced slightly the onset of the degradation temperature of the electrospun nanofibers.